1983
DOI: 10.1029/jb088is01p0b165
|View full text |Cite
|
Sign up to set email alerts
|

Pieces of the ancient lunar crust: Ages and composition of clasts in consortium breccia 67915

Abstract: We discuss the composition and chronology of clasts representing three minor lithologies in consortium breccia 67915. The lithologies studied are: sodic ferrogabbro, pristine troctolitic anorthosite (67915,26), and granulitic troctolitic anorthosite (67915,67). These lithologies were presumed to represent samples of the ancient lunar crust. The pristine troctolitic anorthosite, a typical member of the pristine anorthosite suite, contains little or no trapped liquid consistent with its two‐phase mineralogy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Krähenbü hl et al (1973) and Ganapathy et al (1974) reported siderophile concentrations for white (0.346 ng/g Re, 3.57 ng/g Ir, 1.06 ng/g Au) and grey (0.67 ng/g Re, 7.33 ng/g Ir, 1.9 ng/g Au) lithologies. Ar-Ar plateau ages between 3.91 and 4.10 Ga have been reported (Kirsten et al, 1973;Marti et al, 1983).…”
Section: Lunar Granulitesmentioning
confidence: 88%
“…Krähenbü hl et al (1973) and Ganapathy et al (1974) reported siderophile concentrations for white (0.346 ng/g Re, 3.57 ng/g Ir, 1.06 ng/g Au) and grey (0.67 ng/g Re, 7.33 ng/g Ir, 1.9 ng/g Au) lithologies. Ar-Ar plateau ages between 3.91 and 4.10 Ga have been reported (Kirsten et al, 1973;Marti et al, 1983).…”
Section: Lunar Granulitesmentioning
confidence: 88%
“…Further, it occurred after the crystallization of shallow Mg-suite plutonic rocks. This could be tied to the 4.03-4.1 Ga Ar-Ar age of the troctolite clast in 67915,149 (Venkatesan and Alexander, 1976;Marti et al, 1983). Although this age could also represent an age reset by impact or other post-crystallization event.…”
Section: Crustal Environments For Sulfur Mineralizationmentioning
confidence: 96%
“…Only Ar-Ar age dates have been determined for these clasts. The troctolitic anorthosites have Ar-Ar ages of 4.03-4.1 Ga (Venkatesan and Alexander, 1976;Marti et al, 1983).…”
Section: Descriptions Of 67016 and 67195mentioning
confidence: 97%
“…er Mg 0 (30), and lower Al 2 O 3 (10.2 wt% vs. 12.9 wt%) than this glass group (Lindstrom and Salpas, 1983;Marti et al, 1983). Quartz monzogabbros typically have lower TiO 2 (<2 wt%), higher FeO (usually >14 wt%), and usually much higher P 2 O 5 (commonly upwards of several wt%).…”
Section: Basaltic-andesite Glassesmentioning
confidence: 96%
“…No material is an exact match, although Warren's (1989) high-K KREEP and the Apollo 16 alkali gabbronorite (AGN; Jolliff, 1998) have similar shapes. Apollo 16 sodic ferrogabbro (SFG) data are from Marti et al (1983) and Lindstrom and Salpas (1983). All other data are from Jolliff (1998) …”
Section: Ungrouped Glassesmentioning
confidence: 99%